Three new species of Mesonemoura (Plecoptera: Nemouridae) from China - Li, Weihai; Cui, Jianxin; Yang, Ding (Zootaxa, 2017)
Three new species of the stonefly genus Mesonemoura, M. bispina sp. nov., M. trapezoidea sp. nov., and M. zwicki sp. nov., are described from China. Genitalic similarities with related species are discussed. The types are deposited in the Entomological Museum of China Agricultural University, Beijing and Henan Institute of Science and Technology, Xinxiang, respectively.